2022
DOI: 10.3390/foods11152201
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Stability and Texture of Soybean-Oil-Body-Substituted Low-Fat Mayonnaise: Effects of Thickeners and Storage Temperatures

Abstract: With the increasing consumer demand for low-fat and low-cholesterol foods, low-fat mayonnaise prepared from soybean oil body (SOB) substitute for egg yolk has great consumption potential. However, based on previous studies, it was found that the stability and sensory properties of mayonnaise substituted with SOB were affected due to there being less lecithin and SOB containing more water. Therefore, this study investigated the effects of different ratios of xanthan gum, pectin and modified starch as stabilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…This is because oxidation reactions can cause the breakdown of pigments, resulting in a decrease in the a* value. Similar results were reported by a study using brewer's yeast as a fat replacer in mayonnaise, which depicted that the a* value of mayonnaise was observed as unfavourable for most of the samples, indicating a slight green colour of mayonnaise samples (Worrasinchai et al, 2006).…”
Section: Colour Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…This is because oxidation reactions can cause the breakdown of pigments, resulting in a decrease in the a* value. Similar results were reported by a study using brewer's yeast as a fat replacer in mayonnaise, which depicted that the a* value of mayonnaise was observed as unfavourable for most of the samples, indicating a slight green colour of mayonnaise samples (Worrasinchai et al, 2006).…”
Section: Colour Parameterssupporting
confidence: 88%
“…Additionally, the loss tangent (tan δ) observed for all samples was in the range of 0.39-0.30, and this range was reduced to 0.33-0.27 on day 21. A previous study reported that a poor gel-like quality characterises this behaviour and the rheological attributes of other products and condiments (Worrasinchai et al, 2006). The control sample demonstrated a two-fold greater G 0 value (550 Pa) with a comparable G 00 value (220 Pa), and the data observed for SPP-supplemented samples depicted that both storage and loss moduli were significantly (P < 0.05) improved with increasing concentration of SPP.…”
Section: Viscoelastic Propertiesmentioning
confidence: 67%
See 1 more Smart Citation
“…The linolenic acid content (1.7% on average) was higher than that of the OB (0.9%, Table 1 ) thanks to the soymilk fat contribution. The increased value of this fatty acid improved the functional potential of mayonnaise due to the ω-3 fatty acids are strongly associated with a minor risk of cardiovascular diseases, control of long-term glycaemic index and insulin resistance [ 41 ]. In this regard, it is known that the ideal ω-6/ω-3 ratio should be 4:1, while it was calculated to be about 13:1 in the proposed mayonnaise.…”
Section: Resultsmentioning
confidence: 99%
“…The determination of color properties of the ice cream samples (−18 °C) were according to the previously reported method [ 22 ], including lightness ( L* ), red-green value ( a* ), and yellow-blue value ( b* ), by a colorimeter at the temperature of 4 °C (ZE6000, Nippon Denshoku, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%